Pemanfaatan Pasta Sukun (Artocarpus altilis) pada Pembuatan Mi Kering - Novi Safriani; Ryan Moulana; Ferizal Ferizal (Agricultural Faculty, 2013)
The aim of this study was to determine the best treatment combination between the ratio of wheat flour and breadfruit pasta, and the combination of the drying temperature and time to produce dried noodles with good quality and preferred by consumers. The effect of the ratio of wheat flour and breadfruit pasta (70:30%, 60:40%, and 50:50%), and the combination of the drying temperature and time (60°C, 70 minutes and 70°C, 60 minutes) on the quality of the dried noodles were investigated. The results showed that the best quality of the dried noodles based on the organoleptic and cooking quality test obtained from the combination of the treatment of ratio of wheat flour and breadfruit pasta = 70:30% and the combination of drying temperature and time = 700C for 60 minutes with the following characteristics: water content of 8,78%, fat content of 13,67%, protein content of 11.90%, ash content of 1,35%, and carbohydrate content of 65,22%. The organoleptic value of the best dried noodles before rehydration: color of 2,75; flavor of 2,83; texture of 2,73; whereas after the rehydration, the best dried noodles has organoleptic values: color of 2,81; flavor of 2,92; and taste of 2,77.